Assessment of Knowledge Level about Acquired Immune Deficiency Syndrome and Patient Approaches of Dental Students - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Background: The aim of this study was to evaluate the level of knowledge about HIV, and intraoral signs that can be seen in HIV positive patients and the interpretation of attitudes toward HIV positive patients of fourth-and fifth-grade students at Marmara University Faculty of Dentistry, Istanbul, Turkey. Material and Methods: In our study, a questionnaire consisting of 23 questions was applied to 100 fourth-and 100 fifth-grade students totalling 200 dental students who are educated in Marmara University Faculty of Dentistry. Besides the knowledge level of the students, their attitudes were evaluated using the survey conducted. Chi-square (or Fisher's exact test at appropriate locations) was used to examine the relationship between categorical variables. Statistical significance level was determined as P < 0.05. Results: Of the 200 participants, 46 (23.0%) were males and 154 (77.0%) were females. One hundred people (50%) are fourth grade, 100 people (50%) are fifth grade. The rate of fifth grade agreements for the question Treatment of HIV positive patient increases the risk of transmission of HIV infection to dentist was statistically higher than that of fourth-grade students (Fisher's exact P < 0,05). Fifth-grade knowledge of oral symptoms of HIV/AIDS was statistically higher than fourth grades (Fisher's exact P < 0.05). Conclusion: As the grade level increases, the knowledge about HIV/AIDS raises portraying a relevant approach to patients with AIDS. Comprehensive training and motivation for improving dentistry students' awareness against HIV-positive patients will also improve knowledge and attitudes of the students that enable them to take better care of HIV-positive patients.
Keywords: Acquired immune deficiency syndrome; awareness; human immunodeficiency virus; oral findings; HIV-INFECTION; ATTITUDES; HIV/AIDS; TURKEY